2020
DOI: 10.1016/j.ctro.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and volumetric outcomes of combining cyst puncture through an Ommaya reservoir with index-optimized hypofractionated stereotactic radiotherapy in the treatment of craniopharyngioma

Abstract: Large cystic craniopharyngioma management combining cyst puncture through an Ommaya reservoir with hypofractionated stereotactic radiotherapy was evaluated. The planning optimization was focused on the gradient and selectivity. Punctured and filled cyst treatment plans were compared with a retrospective analysis of volumetric and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…To overcome this recurrent complication, a catheter or, more preferably, ORS insertion is recommended. 18,[25][26][27] Chemotherapy had no role in our study. In Mansour et al 20 and Rachinger et al, 28 chemotherapy also had no role.…”
Section: Discussionmentioning
confidence: 88%
“…To overcome this recurrent complication, a catheter or, more preferably, ORS insertion is recommended. 18,[25][26][27] Chemotherapy had no role in our study. In Mansour et al 20 and Rachinger et al, 28 chemotherapy also had no role.…”
Section: Discussionmentioning
confidence: 88%
“…[9] An analysis of adult patients with cystic craniopharyngiomas concluded that the use of the Ommaya reservoir with SRT could minimize radiation exposure to the optic apparatus and brain stem. [8,12,15] In this study, only one tumor was identified to have enlarged and categorized as TP, which was mainly a cystic lesion. We selected FSRT because the tumor compressed the optic nerve.…”
Section: Discussionmentioning
confidence: 95%
“…The previous studies have indicated tumor enlargement during or after the treatment, especially in craniopharyngiomas with cystic components. [ 1 , 8 , 12 ] A group of pediatric patients with this tumor received proton beam therapy and intensity-modulated RT after RT. In 52 patients, 40% had cyst growth during RT and 20% required intervention such as cyst decompression or adaptive replanning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of adjuvant radiotherapy may facilitate local tumor control after Ommaya catheter placement for cystic craniopharyngiomas [73][74][75][76]. A recent case series of six patients by Laville et al found favorable local tumor control at 12-month follow-up after combined Ommaya reservoir placement and hypofractionated radiotherapy at lower doses of radiation than would be required had the cyst not been drained [77]. Likewise, Jarebi et al also described a patient in whom stereotactic Ommaya reservoir placement and adjuvant radiosurgery of the solid component of a cystic craniopharyngioma successfully alleviated visual deficits and intracranial hypertension without the need for open surgery [71].…”
Section: Stereotactic Cyst Decompressionmentioning
confidence: 99%